IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DENGAN MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI PEMANASAN GLOBAL DI KELAS XI SMAN 1 BONAI DARUSSALAM - Siti Fadila; Mitri Irianti; M Nor M Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study is to improve students' cognitive learning outcomes byimplementing a cooperative learning model of Think Talk Write type with mind mapping onglobal warming material for class XI of SMAN 1 Bonai Darussalam. The type of research used isa quasi-experimental design with one group being given treatment and one group not beinggiven any treatment. The research population was all students of class XI SMAN 1 BonaiDarussalam in the academic year 2021/2022, totaling 27 students and the research sampletotaling 15 students. The research instrument used was a test of students' cognitive learningoutcomes. The data collection technique in this study was to provide cognitive learning outcomestests after the learning process was carried out. The data were analyzed using descriptiveanalysis by calculating the absorption and effectiveness of learning, and inferential analysis ofhypothesis testing by means of t-test using the IBM SPSS Statistics 23 program. The results ofthis study were that there were differences in the cognitive learning outcomes of students whoapplied the Think Talk Write cooperative learning model. with Mind Mapping by applyingconventional learning, while the average absorption power of the experimental class is 82.22%in the good category and the control class is 68.29% in the fairly good category with a differencein value of 13.93%. The effectiveness of learning in the experimental class is in the effectivecategory and the control class is in the quite effective category. Thus the implementation of theThink Talk Write type cooperative learning model with Mind Mapping can improve students'cognitive learning outcomesKeywords: Cognitive Learning Outcomes, Think Talk Write, Mind Mapping, Global Warming